1996
DOI: 10.1161/01.cir.93.11.2080
|View full text |Cite
|
Sign up to set email alerts
|

Change in Aortic End-Systolic Pressure by Alterations in Loading Sequence and Its Relation to Left Ventricular Isovolumic Relaxation

Abstract: Descending intervention induced greater prolongation of T than ascending intervention. Prolongation of T was closely related to an increase in AoESP in the descending intervention but a decrease in AoESP in the ascending intervention. These data suggest that not only the loading sequence but also the pressure level at the onset of isovolumic relaxation determines LV relaxation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
38
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 29 publications
1
38
0
Order By: Relevance
“…During early ejection, active development of fiber crossbridges occurs in the myocardium, whereas a transition from contraction to relaxation occurs in mid-to-late systole, during which increases in load may be particularly deleterious, leading to more hypertrophy and abnormal diastolic relaxation. 2,33 The differential effect of time-varying myocardial afterload on cellular processes taking place in early and late ejection is, therefore, an important area for future research.…”
Section: Discussionmentioning
confidence: 99%
“…During early ejection, active development of fiber crossbridges occurs in the myocardium, whereas a transition from contraction to relaxation occurs in mid-to-late systole, during which increases in load may be particularly deleterious, leading to more hypertrophy and abnormal diastolic relaxation. 2,33 The differential effect of time-varying myocardial afterload on cellular processes taking place in early and late ejection is, therefore, an important area for future research.…”
Section: Discussionmentioning
confidence: 99%
“…16 Excessive pressure pulsatility and premature wave reflection have a deleterious effect on left ventricular systolic and diastolic function, leading to atrial and ventricular remodeling and hypertrophy. 17,18 Natriuretic peptide and adrenomedullin levels have important and complex associations with measures of arterial stiffness. Atrial natriuretic peptide (ANP) and B-type natriuretic peptide (BNP) are released by the heart in response to atrial and ventricular loading conditions, respectively, 19 and act to reduce overload by virtue of their natriuretic properties.…”
Section: Clinical Perspective P 3085mentioning
confidence: 99%
“…Although animal and small human studies have shown that an acute increase in LV afterload, particularly in late-systolic load, adversely impacts on LV early diastolic relaxation, [8][9][10][11][12] little is known about its chronic effect on LV diastolic function. We hypothesized that enhanced late-systolic load may be associated with altered LV diastolic function at steady state.…”
mentioning
confidence: 99%